Decoration of NiFe‐LDH Nanodots Endows Lower Fe‐d Band Center of Fe1‐N‐C Hollow Nanorods as Bifunctional Oxygen Electrocatalysts with Small Overpotential Gap - Liu, Zheng‐Qi; Liang, Xiongyi; Ma, Fei‐Xiang; Xiong, Yu‐Xuan; Zhang, Guobin; Chen, Guohua; Zhen, Liang; Xu, Cheng‐Yan (Advanced energy materials, 2023)
Single‐atom Fe‐N‐C (denoted as Fe1‐N‐C) catalysts exhibit inadequate bifunctional activities to conquer the sluggish oxygen reduction and evolution reaction (ORR/OER), hindering their practical applications in rechargeable Zn‐air batteries (ZABs). Here, by employing Fe1‐N‐C hollow nanorods as ORR‐active support, OER‐active NiFe‐layered double hydroxide (NiFe‐LDH) nanodots are evenly decorated through a spatially confined process to form NiFe‐LDH/Fe1‐N‐C heterostructure hollow nanorods with abundant accessible catalytic sites. The NiFe‐LDH/Fe1‐N‐C heterostructure not only enhances the ORR activity of pristine Fe1‐N‐C but also realizes efficient bifunctional ORR/OER activity in one monolithic catalyst. Theoretical calculations reveal that introducing NiFe‐LDH nanodots results in donation of electrons to the Fe1‐N‐C matrix and thus lowers the Fe‐d band center of the Fe‐N4 sites, dramatically narrowing the energy barriers of the ORR rate‐limiting steps. As a result, NiFe‐LDH/Fe1‐N‐C nanorods deliver remarkable ORR activity with a half‐wave potential of 0.90 V versus reversible hydrogen electrode, surpassing bare Fe1‐N‐C and commercial Pt/C. Impressively, the integrated NiFe‐LDH/Fe1‐N‐C catalysts show outstanding bifunctional performance with a small overpotential gap of only 0.65 V. The liquid‐state ZABs with NiFe‐LDH/Fe1‐N‐C as an air‐cathode catalyst deliver a peak power density of 205 mW cm−2 and long‐term cycling stability of up to 400 h. Oxygen evolution reaction (OER)‐active NiFe‐layered double hydroxide (LDH) nanodots are evenly decorated on the oxygen reduction reaction (ORR)‐active Fe1‐N‐C hollow nanorods to realize bifunctional ORR/OER activity in one monolithic catalyst with a small overpotential gap of only 0.65 V. NiFe‐LDH regulates the electronic structures of Fe1‐N‐C by transferring electrons to the Fe‐N4‐active sites and thus significantly reduces the energy barrier of the rate‐determining step during the ORR.